An improved 2D modeling of bearing based on DEM for predicting mechanical stresses in dynamic. (July 2017) - Machado, C.; Guessasma, M.; Bellenger, E.
Highlights: Bearing model based on DEM is proposed in 2D. An entirely description of bearing taking into account rolling elements, cage and rings is developed. Elastic rings, rigid and flexible housings are considered. Load distributions and Von Mises stresses are studied and compared with FEM in static. Load distributions and Von Mises stresses are computed in dynamic. Abstract: This paper presents an original approach using Discrete Element Method (DEM) for predicting the mechanical behavior of a bearing considering rigid and elastic housing. The ability of DEM to describe accurately the mechanical state of a bearinghas been established by means of a comparison with FEM, of mechanical stresses and load distributions in a static case. Specifically, a contact model and a cohesive model are implemented together in 2D simulations. Once static results validated, DEM simulations are conducted in dynamic in order to evaluate Von Mises stresses within the rings. The bearing is decomposed in a macroscopic polydisperse granular media made of rolling elements and cage components. The rings are modeled as a homogeneous continuous material by considering a cohesive granular assembly. Besides the fact that the proposed modeling takes into account all bearing components, it also allows to describe both elastic behavior and loading evolution in dynamic mode.